Interleukin-6 as an Indicator for Acute Toxicity of DBL2β-PfEMP1 Recombinant protein as a Peptide-based Malaria Vaccine Candidate - Sari, Leny Yulia Widia; Sulistyaningsih, Erma; Siswoyo, Tri Agus (Jurnal ILMU DASAR, 2025)
Malaria caused by Plasmodium spp is an important health problem, and vaccination could be essential for disease prevention. One potential protein candidate is the Duffy binding-like 2β (DBL2β)-Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1). The protein is responsible for malaria pathogenesis by mediating binding to intercellular adhesion molecule-1 (ICAM-1), a receptor on the host cells. This study aimed to investigate the acute toxicity of the DBL2β-PfEMP1 recombinant protein as a basis for developing a peptide-based malaria vaccine based on body weight and interleukin-6 (IL-6) concentration. The study used male and female Wistar rats, which were divided into treatment and control groups after two weeks of acclimatization. Rats in the treatment group were injected with 750 µg DBL2β-PfEMP1 recombinant protein, and the control group was injected with NaCl 0.9%. Any indications of clinical toxicity symptoms were closely monitored within 4 hours of injection up to 24 hours. Observations were conducted daily for 14 days and included body weight and toxicity symptoms such as rising fur, tremors, salivation, diarrhea, weakness, draping, excitability, twitching, and death. Blood was collected on days 5, 7, and 14 for IL-6 examination using the ELISA method. Rats were euthanized on day 14. Data were analyzed using an ANOVA test. There was no significant weight loss as well as weight gain and toxicity symptoms during 14 days after treatment in all groups. There was an increase IL-6 levels on day 14 in all groups. However, statistical analysis did not show a significant difference between the control and treatment groups (p>0.05). This study showed that the DBL2β-PfEMP1 recombinant protein has no acute toxicity in Wistar rats, implying its safety and potential as a peptide-based malaria vaccine.